Factor Analysis of Musculoskeletal System Complaints on Horticultural Farmers Spraying Pesticides in Sako Duo Village, Kerinci - Melda Yenni; Novi Berliana; Mila Mustika (Riset Informasi Kesehatan, 2022)
Background: The agricultural sector is a high-risk occupation, health problems that are often experienced by farmers are MSDs complaints. The results of the initial survey of BPS (Central Bureau of Statistics) found that 80% of farmers suffer from back pain. The purpose of this study was to determine the relationship between work posture, workload, length of work and body size with complaints of the musculoskeletal system when spraying pesticides on horticultural farmers in Sako Dua village. Metode: This study is a quantitative study using a cross sectional design. The research population was all members of the farmer group as many as 191 farmers and the research sample was 51 farmers who sprayed pesticides. The sampling technique used was the purposive sampling technique. The research instrument used a questionnaire and measurement sheets. The research technique used interviews and measurements with REBA, Nhon Hoa sitting scales, Electronic Personal Scale, and Stature Meters. Data were analyzed by univariate and bivariate using chi-square test. Results : 60.8% of respondents experienced high MSDs complaints, 68.6% of respondents experienced high risk work postures, 94.1% of respondents had additional workloads in the heavy category, 72.5% of respondents had long work durations, and 41.2% of respondents had Obese BMI. Bivariate results show that there is a relationship between work posture and MSDs complaints (p-value = 0.000), there is no relationship between additional workload (p-value = 0.315), there is a relationship between length of work (p-value = 0.000), and there is no relationship between BMI (p-value=0.398) with MSDs complaints. Conclusion : MSDs disorders can occur due to several factors such as inappropriate body posture, heavy workload coupled with a spraying equipment load that weighs more than 10 kg, long working hours that are not accompanied by adequate rest and other risk factors. tendency to fatigue, illness, accidents and an increased risk of MSDs. Farmers have received counseling every 3 months but not from health workers and not counseling related to ergonomics or work postures.